Alterações na matriz extracelular em modelo animal da doença de Peyronie e os efeitos do tratamento pelo Micofenolato Mofetil - Antoniassi, Thiago da Silveira (2024)
Introduction: Peyronie's disease is a benign condition characterized by an acquired penile abnormality due to fibrosis of the tunica albuginea, which may lead to penile pain, tortuosity and deformation of the penis, as well as impairment of the patient's sexual activity. Since its etiology is not fully understood, the treatment strategies are difficult. The lack of effectiveness of oral drugs or topical treatment encourages new trials to establish the mechanisms of the disease and new treatments. Aim: To evaluate the histological, histochemical, and stereological changes caused by Mycophenolate Mofetil (MMF) on the tunica albuginea of the rats´ peniles submitted to TGFPeyronie's Disease induction. Methods: Twenty-six adult male Wistar rats, weighing on average 381 g., were divided into five groups. Group Control: animals free of experimental handling; Group SHAM: animals received an injection of saline solution 0,9%; Group TGF- : animals received an injection of TGF- and euthanized after seven days of induction; Group TGF- : animals received an injection of TGF- and euthanized after 30 days of induction; Group TGF- : animals treated with MMF for seven days after induction with TGF- Group TGF- : animals treated with MMF for 30 days after induction with TGFand euthanized after this period. The processing of histological sections was analyzed in a conventional light microscope and fluorescence system coupled with the same microscope. The stereological evaluation included the relative volume of different types of connective fibers of the penile tunica albuginea. Analysis of Matrix Metalloproteinases (MMP) and stromal cellular elements was performed by immunohistochemistry (IHC) of the tunica albuginea. Statistical analyses were performed considering p<0.05 statistically significant. Parametric data were analyzed by one-way ANOVA followed by Tukey's test and non-parametric data by Kruskal- od followed by Dunn's test. Results: In the histochemical evaluation, we found changes in the quantity and ratio of collagen III/I during PD induction with a return to the initial pattern after treatment with MMF. Elastic fibers were scattered during PD induction, but MMF treatment potentially reduced structural damage. Proteoglycans were remodeled in the tunica albuginea after PD induction. In the immunohistochemistry evaluation, matrix metalloproteinases (MMPs) were expressed differently after induction of PD and in treatment with MMF; there was a change in the proportion of fibroblasts/myofibroblasts after treatment with MMF. Conclusions: generate fibrotic changes in the extracellular matrix coinciding with the findings of PD.MMF acted as an antifibrotic agent, remodeling extracellular matrix elements. The results have shown us the effective participation of proteoglycans and especially MMPs in the disease genesis process and mitigation of the effects with MMF treatment.